Unveiling the recent advancements of polymetallic alloys electrocatalysts for hydrogen generation and storage - Sumbul Raza; Iqra Sadiq; Saman Shaheen; Mariyam Saniya; Tokeer Ahmad (Sustainability Science and Technology)
Advancement of new materials for hydrogen generation and storage under mild conditions has very high desirability in both application and fundamental aspects. One of the main reasons to attain large scale hydrogen production is the accessibility of highly stable and active electrocatalysts. Alloy strategies can embrace the hardships of enhancing electrocatalysts activity and optimizing their costs. In this review, recent developments on alloy based electrocatalysts for hydrogen evolution and storage have been thoroughly discussed. Firstly, the advancements in the synthesis of alloy based electrocatalysts have been reviewed, afterwards the recent reports on binary and ternary alloy electrocatalysts for hydrogen evolution reaction and storage have been summarized. However, for their adoption at an industrial scale, it is important to ensure that these electrocatalysts demonstrate long-term stability and sustainability. While this work highlights the exceptional properties of alloy-based electrocatalysts, it also addresses the remaining challenges, such as scalability, durability, and cost-effectiveness that must be overcome to fully realize their potential in practical applications.